The soil - Yi, Kwang-su 1892- (Library of Korean literature ;, 2013)
"A major, never before translated novel by the author of Mujông / The Heartless -- often called the first modern Korean novel -- The Soil tells the story of an idealist dedicating his life to helping the inhabitants of the rural community in which he was raised. Striving to influence the poor farmers of the time to improve their lots, become self-reliant, and thus indirectly change the reality of colonial life on the Korean peninsula, The Soil was vitally important to the social movements of the time, echoing the effects and reception of such English-language novels as Upton Sinclair's The Jungle"--